The role of management commitment of service quality through job embeddedness on service recovery performance / Norhamizan Hamir - Hamir, Norhamizan; Salleh, Rashid; Mohd Said, Noraslinda; Ariffin, Hashim Fadzil; Ahmad, Zamri (Universiti Teknologi Mara Cawangan Pulau Pinang, 2020)
Service recovery is a corrective action that is carried out immediately by the service provider if the service offered went wrong. The employee is responsible to handle the situation in order to ensure that the customer who might not be satisfied with the situation that happens turns to be satisfied. One of the concepts of the service recovery that have been discussed in the literature is related to service recovery performance. The researcher defined that service recovery performance is to focus on the performance of frontline employees. Service recovery performance is not about a strategy or action to handle a service recovery situation which among others are an apology, giving discounted price and compensation but more towards the behavior of the frontline employees getting engage in resolving the situation. Past researchers have identified that the management commitment to service quality which represented by several indicators may lead to the service recovery performance of the employees. However, the relationship has a missing link. The objective of this conceptual paper is to further discuss the relationship between management commitment to service quality and service recovery performance with the present mediating role of job embeddedness among frontline hotel employees in four and a five-star hotels. The proposition suggested in this paper may require support with further empirical findings to be carried out.